Agricultural Extension and "in Schools of Farm Clown "in Mozambique: The Production Case Horticultural Areas Green Maputo City (Revista Brasileira Multidisciplinar, 2010)
A sample survey of 68 farmers representing the same amount of households was created to study the impact of crop diversification and access to extension services on on-farm income of horticultural producers in Zonas verdes (Maputo-Mozambique). Results indicate that there was no significant difference between the income of male and female producers. On the other hand, the level of crop diversification is still low and the impact of extension assistance has not yet brought appreciable changes on farmers' income.
Keywords: Horticultural income; Extension assistance; Crop diversification.